Controlled intracellular trafficking alleviates an expression bottleneck in S. cerevisiae ester biosynthesis - Zhu, Jie; Schwartz, Cory; Wheeldon, Ian (Metabolic engineering communications, 2019)
In metabolic engineering, most available pathway engineering strategies aim to control enzyme expression by making changes at the transcriptional level with an underlying assumption that translation and functional expression follow suit. In this work, we engineer expression of a key reaction step in medium chain ester biosynthesis that does not follow this common assumption. The native Saccharomyces cerevisiae alcohol acyltransferses Eeb1 and Eht1 condense acyl-CoAs with ethanol to produce the corresponding ester, a reaction that is rate limiting in engineering ester biosynthesis pathways. By changing the N- and C-termini of Eeb1 to those of Eht1, Eeb1 localization is changed from the mitochondria to lipid droplets. The change has no significant effect on transcription, but increases protein expression by 23-fold thus enabling a 3-fold increase in enzyme activity. This system demonstrates one example of the impact of protein trafficking on functional pathway expression, and will guide future metabolic engineering of ester biosynthesis and, potentially, other pathways with critical membrane-bound enzymes. •Intracellular localization can control membrane-associated enzyme expression.•Terminal domain swapping of Eht1 and Eeb1 alters intracellular localization.•Eeb1 expression and activity are increased with lipid droplet targeting.